Network effects and switching costs in the US wireless industry: Disentangling sources of consumer inertia - Stefan Weiergräber (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
I develop an empirical framework to disentangle different sources of consumer inertia in the US wireless industry. The use of a detailed data set allows me to identify preference heterogeneity from consumer type-specific market shares and switching costs from churn rates. Identification of a localized network effect comes from comparing the dynamics of distinct local markets. The central condition for identification is that neither the characteristics defining consumer heterogeneity nor the characteristics defining reference groups are a (weak) subset of the other. Being able to separate switching costs and network effects is important as both can lead to inefficient consumer inertia, but depending on its sources policy implications may be very different. Estimates of switching costs range from US- 316 to US- 630. The willingness to pay for a 20%-point increase in an operator's market share is on average US- 22 per month. My counterfactuals illustrate that both effects are important determinants of consumers' price elasticities potentially translating into market power that helps large carriers in defending their dominant position.
urn:nbn:de:bvb:19-epub-25094-1
Keywords: 330